Diagnóstico físico conservacionista como subsídio para o manejo e recuperação de áreas degradadas na bacia hidrográfica do médio curso do rio Jaguaribe (CE) - Brasil - Albuquerque, Amanda Menezes de (2021)
The hydrographic basin of the Middle Jaguaribe (CE) has the Jaguaribe River as its main, with a course of approximately 171 km in length between the valve of the Orós weir and the Peixe Gordo bridge, on the BR-116. The research aims to analyze the process of environmental degradation through the Physical Conservationist Diagnosis as a subsidy for the management and recovery of these areas, as it is a well-defined natural system in the space where physical interactions are integrated and, therefore, , easier to be understood, spatialized and characterized. For the elaboration of the study, bibliographical survey, field activities, compilation of data with competent bodies, characterization of the physical environment of the basin were carried out, in addition to geological, geomorphological, hydrological, climatic and pedological analyzes. The applied methodology included the analysis of parameters, such as: Climate Index, Rain Erosivity, Soil Erodibility, Average Declivity, Drainage Density and Vegetation Coverage Index. The result of the study was expressed in a descriptive formula showing the sectors of the basin and the degree of conservation of natural resources. The answers were obtained through the analysis of cover and land use, between the years 1992 and 2018 as a way to expose the transformations resulting from the anthropic action, and consequently, the increase in degradation. Through the results found, it was observed that, the process of environmental deterioration in the scope of the basin has been evolving over the selected historical period, sector A with a rate of degradation (23.3%), followed by sector B (23.8%) %) and sector C (22.4%) which, even with the lowest index, presented the greatest variation in the degree of coverage and land use